High Performance Gas Diffusion Layer with Hydrophobic Nano layer under a Supersaturated Operation Condition for Fuel Cells - Ko, Tae-Jun; Kim, Sae Hoon; Hong, Bo Ki; Lee, Kwang-Ryeol; Oh, Kyu Hwan; Moon, Myoung-Woon (American Chemical Society, 2015)
Reliable operation of a proton exchange membrane fuel cell requires proper water management to prevent water flooding in porous carbon materials such as the gas diffusion layer (GDL). In contrast to the conventional GDL that uses the "wet" dip-coating process with solvent and expensive polytetrafluoroethylene, we have proposed a novel GDL with a controlled hydrophobic silicone (i.e., hexamethyldisiloxane) nanolayer by a highly efficient and cost-effective "dry" deposition process. The GDL with the nanolayer exhibited an increased contact angle, decreased contact angle hysteresis, and suppressed water condensation. Even though the GDL with the nanolayer had a higher electrical resistance than the pristine GDL, the cell performance of the GDL with an optimum nanolayer thickness of 8.6 nm was practically the same as that of the pristine GDL under normal operating conditions. Under a supersaturated condition, the GDL with optimum nanolayer thickness exhibited much higher cell performance than the pristine GDL over all current densities due to enhanced hydrophobicity. Long-term operational stability and dynamic response of the GDL with the nanolayer were much improved over those of the pristine GDL.
Keywords: RELATIVE-HUMIDITY; PLASMA TREATMENT; ELECTRODE; TEMPERATURE; SURFACES; KINETICS; MEDIA; GDL